RandD paths of pixel detectors for vertex tracking and radiation imaging - Battaglia, M; Da Via, C; Bortoletto, D; Brenner, R; Campbell, M; Collins, P; Dalla Betta, G; Demarteau, M; Denes, P; Graafsma, H; Gregor, I; Kluge, A; et al. (2013)
This report reviews current trends in the RandD of semiconductor pixellated sensors for vertex tracking and radiation imaging. It identifies requirements of future HEP experiments at colliders, needed technological breakthroughs and highlights the relation to radiation detection and imaging applications in other fields of science. © 2013 Elsevier B.V.